Identify the most significant variables that influence the economic efficiency in a productive company - Moica Sorina; Harpa Elena (Scientific Bulletin of the ''Petru Maior" University of Tîrgu Mureș, 2014)
Measuring economic efficiency becomes one of the major problems for the persons involved in the production management. The purpose of this paper is to present the result concerning the Economic Efficiency indicator, which was done in a survey realize during then month’s period in a SME. Because the Economic Efficiency indicator is calculated taking in consideration several variables, we chose to analyze the production variable without taking in consideration the price information. Our approach taken was to identify the variables that represent the technical efficiency and the main findings is that from thirteen variables we identify the most important six.